Effect of RvD1/FPR2 on inflammatory response in chorioamnionitis. Issue 22 (6th October 2020) - Li, Anna; Zhang, Lin; Li, Junxia; Fang, Zhenya; Li, Shuxian; Peng, Yanjie; Zhang, Meihua; Wang, Xietong
Abstract: Chorioamnionitis (CAM), as a common intrauterine infectious disease, is the leading cause of premature birth, stillbirth, neonatal infection and sepsis. The formyl peptide receptor 2 (FPR2) is a member of GPCRs widely distributed in a variety of tissues and is associated with many inflammatory diseases. With the discovery of FPR2 in human placenta, the possibility of exploring the function of FPR2 in obstetrics is evolving. The Resolvin D1 (RvD1) plays an important role in the resolution of inflammation by combining with FPR2. In this study, we evaluated the role of FPR2 and RvD1 in CAM, not only in the human placenta but also in mouse models. The expression of FPR2 increased in the placenta of CAM patients and the downstream PPARγ/NF‐κB signalling changed accordingly. Moreover, Fpr2 −/− mice were highly susceptible to LPS, displaying a worse CAM symptom, compared with WT mice. By establishing a model of trophoblast inflammation in vitro, it was confirmed that RvD1 rescued the effect of LPS on inflammation by combining with FPR2 and its downstream PPARγ/NF‐κB pathway. Otherwise, RvD1 improved the preterm labour in a mouse model of CAM induced by LPS. Altogether, these findings show that RvD1 alleviated the inflammation of trophoblast in vivo and in vitro through FPR2/PPARγ/NF‐κB pathway, suggesting RvD1/FPR2 might be a novel therapeutic strategy to alleviate CAM.